Online Education in Early Primary Years: Teachers' Practices and Experiences during the COVID-19 Pandemic - Kleopatra Nikolopoulou (MDPI AG, 2022)
During the COVID-19 pandemic, educational institutions around the world were forced to close and the academic process continued online. Online teaching can support students' learning, but little research exists in the foundational early primary years (children aged 4-8). The purpose of this study was to investigate teachers' practices and experiences in implementing online teaching during the pandemic period. The participants were 14 Greek teachers of early primary years, and data were collected via interviews. The findings indicated that most of the teachers used a combination of teaching practices-approaches, while the learning activities implemented mainly regarded language, psychomotor activities, display of videos, mathematics and interdisciplinary activities. Teachers' feelings were initially negative, while afterwards they experienced more positive feelings. Disadvantages of online education, as experienced by teachers, mainly regarded technical problems, followed by limited resources/support for children at home, and limited training in online methodology. Teachers' positive experiences regarded children's familiarization with the technology and maintenance of contact with the school environment, while the role of the parents was revealed as essential. Implications and suggestions for future online education in early primary years include maintenance of good high-standard teaching practices, enhancement of digital culture and parents' involvement with children's activities at home.